In the Middle: Department Chairs as Mentors and Mentees - Carolyn A. Groff; James F Konopack Dr. (Academic Chairpersons Conference Proceedings, 2018)
Department chairs, especially new chairs, need mentoring as they simultaneously learn to provide mentorship to department faculty. The type of mentoring that department chairs need from their administrators to be successful leaders can differ from the type of mentoring chairs are provide to their faculty colleagues.
Keywords: Mentoring; tenure; promotion; leadership; administration